Sustainable prevention of food crises in Sub-Saharan Africa - Badiane, Ousmane; Collins, Julia; Fujita, Yasuo; Laborde Debucquet, David; Martin, Will; Terero, Maximo; Vos, Rob; Yamauchi, Futoshi (T20, 2019)
Food crises and distress migration will continue to plague the African continent in the decades ahead unless massive investments are made to make the region’s agriculture and food systems more resilient. The G20 should support and invigorate region-wide efforts to: (a) massively expand irrigation systems for smallholder farms to boost agricultural productivity and enhance resilience against the impacts of climate change, (b) achieve a “big push” in infrastructure, technology and finance to develop robust agri-food systems, and (c) enact concerted reforms of agricultural price and trade policies to strengthen trade integration, diversify domestic food supplies, and enhance country-level capacity to adjust to food shortages.